Who was Dr. Seuss? - Pascal, Janet B.; Harrison, Nancy, 1963- (New York, N.Y. : Grosset & Dunlap, 2011)
Ted Geisel loved to doodle from the time he was a kid. He had an offbeat, fun-loving personality. He often threw dinner parties where guests wore outrageous hats! And he donned quirky hats when thinking up ideas for books like his classic The Cat in the Hat. This biography, with black-and-white illustrations throughout, brings an amazingly gifted author/illustrator to life.
Who was Dr. Seuss? -- Goofy machines -- A very fine flying cow -- Boids and beasties -- What I saw on Mulberry Street -- An elephant up a tree -- Private SNAFU -- A moose, a nerd, and the Whos -- 'The Cat in the Hat' arrives -- Grinches and turtles and sneetches -- I speak for the trees -- 'Oh, the Places You'll Go!' -- Timelines -- Bibliography.
Includes bibliographical references (page [105]).
Accelerated Reader AR
Accelerated Reader
Accelerated Reader AR
Reading Counts RC
Keywords: Seuss, -- Dr. -- Juvenile literature; Seuss, -- Dr; Authors, American -- 20th century -- Biography -- Juvenile literature; Illustrators -- United States -- Biography -- Juvenile literature; Children's literature -- Authorship -- Juvenile literature; Authors, American; Illustrators; Children's literature -- Authorship; Children's nonfiction; Biographies